2014
DOI: 10.1007/s10753-014-9971-5
|View full text |Cite
|
Sign up to set email alerts
|

MAPK and NF-κB Pathways Are Involved in Bisphenol A-Induced TNF-α and IL-6 Production in BV2 Microglial Cells

Abstract: Microglial activation has been reported to play an important role in neurodegenerative diseases by producing pro-inflammatory cytokines. Bisphenol A (BPA, 2,2-bis (4-hydroxyphenyl) propane), known as a ubiquitous endocrine-disrupting chemical, is reported to perform both mimic- and anti-estrogen properties; however, whether it affects cytokine production or immune response in central nervous system remains unclear. The present study was aimed to explore whether BPA was involved in inflammatory action and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 61 publications
8
41
0
1
Order By: Relevance
“…There have been numerous studies that indicate that mRNA levels correlate well to protein in steady-state conditions, with a gene-specific lag in protein synthesis [57]. Of interest, when bisphenol A was added to the BV-2 cells, both IL-6 and TNFα mRNA expression were induced, with a corresponding increase in protein levels, as measured by ELISA [58]. Similarly, IMG cells demonstrated a concomitant increase in protein with mRNA induction upon exposure to LPS and IL-4 [28].…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies that indicate that mRNA levels correlate well to protein in steady-state conditions, with a gene-specific lag in protein synthesis [57]. Of interest, when bisphenol A was added to the BV-2 cells, both IL-6 and TNFα mRNA expression were induced, with a corresponding increase in protein levels, as measured by ELISA [58]. Similarly, IMG cells demonstrated a concomitant increase in protein with mRNA induction upon exposure to LPS and IL-4 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators (e.g., TNF-α and IL-1β) can activate multiple intracellular signalling molecules, such as MAPK and NF-κB, and thus trigger the expression of related genes1819. During acute soft tissue injury, skeletal muscle endothelial cells, macrophages, and neutrophils secrete a variety of proinflammatory cytokines and proteases that take part in early inflammation through the NF-κB and MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent studies have suggested the potential role of endocrine-disrupting chemicals such as BPA to modify immune cytokine response; however, most are results from indicated that the addition of BPA in macrophages significantly increased the production of TNF-α and IL-6 through NF-κB signaling pathways (20,21). In contrast, studies that implied inhibitory effect of BPA on cytokine production had experimental settings that pretreated immune cells with BPA followed by infection (bacteria or virus) or stimulation with lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we do not know whether the influence of BPA on TLR-triggered cytokine response is a result of direct effect of BPA on TLR expression or the result of an indirect effect of BPA that disrupted downstream signaling events. Nevertheless, several experimental studies have shown that BPA can alter cytokine production via the P13K/Akt, the MAPK/AP-1, or the NF-κB pathways, whereas no influence was observed on TLR4 surface expression (21,24,25). The observation from our study that IL-10 response to TLR ligands remained unperturbed by BPA concentration might also give indirect evidence that BPA had no direct effect on TLR expression, because theoretically, all cytokine production would have been altered if TLR expression, being the origin of the signaling pathway, was modified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation